(untitled) (GYMNASIUM, 2009)
The path to the top sporting result in handball is long and difficult; it is open only to individuals that have above average motor and physical abilities, suitable and unvarying personal characteristics, moral qualities and other mental aptitudes. External factors, such as organisational and expertise level of the club and coach, also influence the development and success. The beginning and an important part of this path is represented with the training of children and youth and a question: Will the sport of young people utilize its enormous educational potential and turn talents into stars, who will keep winning and at the same time stay happy? It is possible, yet the incorrect approach can result in the loss of handball talents or become a source of negative experiences, stress and pressure. Largely, this depends on a discipline, policy of the sports clubs, associations and society in general; yet mostly it depends on a coach who has daily contact with players in the training process. Handball training is carried out in groups that are usually very heterogeneous and require specific type of work. Differentiation and individualisation are coaching methods for working with a diverse group of handball players. A coach can achieve this by precise organisation of training, which allows practising various exercises within a specific individual task. It is also recommended that several coaches or specialist coaches participate in the work with the youngest age categories.